2017
DOI: 10.1093/pasj/psx034
|View full text |Cite
|
Sign up to set email alerts
|

The shortest periodic and flaring flux variability of a methanol maser emission at 6.7 GHz in G 014.23−00.50

Abstract: We detected flaring flux variability that regularly occurred with the period of 23.9 days on a 6.7 GHz methanol maser emission at V lsr = 25.30 km s −1 in G 014.23−00.50 through highly frequent monitoring using the Hitachi 32-m radio telescope. By analyzing data from 05 January 2013 to 21 January 2016, the periodic variability has persisted in at least 47 cycles, corresponding to ∼1,100 days. The period of 23.9 days is the shortest one observed in masers at around high-mass young stellar objects so far. The fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…To date there are at least 20 known periodic methanol masers Araya et al 2010;Goedhart et al 2014;Fujisawa et al 2014;Szymczak et al 2015;Maswanganye et al 2015;Szymczak et al 2016;Maswanganye et al 2016;Sugiyama et al 2017) including one source which shows quasi-periodic variations in both methanol and formaldehyde (Araya et al 2010). The formaldehyde and methanol variations were simultaneous and showed very close correspondence to each other, which the authors speculated was due to modulation of the infrared radiation field by periodic accretion in a binary system.…”
Section: Introductionmentioning
confidence: 98%
“…To date there are at least 20 known periodic methanol masers Araya et al 2010;Goedhart et al 2014;Fujisawa et al 2014;Szymczak et al 2015;Maswanganye et al 2015;Szymczak et al 2016;Maswanganye et al 2016;Sugiyama et al 2017) including one source which shows quasi-periodic variations in both methanol and formaldehyde (Araya et al 2010). The formaldehyde and methanol variations were simultaneous and showed very close correspondence to each other, which the authors speculated was due to modulation of the infrared radiation field by periodic accretion in a binary system.…”
Section: Introductionmentioning
confidence: 98%
“…Goedhart et al (2004) found seven periodic methanol maser sources with periods beween 132 and 668 d. The great majority of variability is not periodic, at least on timescales that have so far been studied. Periodic variability with shorter periods (∼24 d) has also been discovered (Sugiyama et al 2017).…”
Section: Maser Flaresmentioning
confidence: 92%
“…In the above mentioned HMSFR NGC 6334I all maser lines are flaring: OH, methanol and water [20]. The shortest periodic (a period of 23.9 days) and flaring flux variability of a methanol maser at 6.7 GHz were reported in G014.23−00.50 [38]. Even small radio telescopes are useful in variability studies, as demonstrated by the monitoring of the 22 GHz water maser line in the semiregular variable R Crt, carried out using the Kagoshima 6 m telescope [37].…”
Section: Variability Studiesmentioning
confidence: 95%